2022
DOI: 10.1002/acm2.13858
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method to improve efficiency of patient specific SRS and SBRT QA using 3D secondary dose verification

Abstract: Purpose Patient Specific QA (PSQA) by direct phantom measurement for all intensity modulated radiation therapy (IMRT) cases is labor intensive and an inefficient use of the Medical Physicist's time. The purpose of this work was to develop a hybrid quality assurance (QA) technique utilizing 3D dose verification as a screening tool to determine if a measurement is necessary. Methods This study utilized Sun Nuclear DoseCHECK (DC), a 3D secondary verification software, and Fraction 0, a trajectory log IMRT QA soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection 20,34,35 . O'Daniel et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection 20,34,35 . O'Daniel et al.…”
Section: Discussionmentioning
confidence: 92%
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection. 20,34,35 O'Daniel et al assessed the effective risk reduction of combinations of QA methods for IMRT/VMAT treatments. 34 They showed that the MC-based secondary dose calculation was available to reduce the overall risk.…”
Section: Discussionmentioning
confidence: 99%